2020
DOI: 10.1111/jam.14833
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for lactic acid bacteria screening to enhance silage quality

Abstract: The main challenge of ensiling is conserving the feed through a fermentative process that results in high nutritional and microbiological quality while minimizing fermentative losses. This challenge is of growing interest to farmers, industry and research and involves the use of additives to improve the fermentation process and preserve the ensiled material. Most studies involved microbial additives; lactic acid bacteria (LAB) have been the focus of much research and have been widely used. Currently, LABs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 81 publications
0
28
0
2
Order By: Relevance
“…The different results observed are due to the different species and even strains inoculated in the silages (Carvalho et al . 2020). The performance of enzymes is influenced by the composition of the product (combination of different types of enzymes), the composition of the substrate (forage), the dose applied and the conditions of the performance medium such as pH and temperature (Ying et al .…”
Section: Resultsmentioning
confidence: 99%
“…The different results observed are due to the different species and even strains inoculated in the silages (Carvalho et al . 2020). The performance of enzymes is influenced by the composition of the product (combination of different types of enzymes), the composition of the substrate (forage), the dose applied and the conditions of the performance medium such as pH and temperature (Ying et al .…”
Section: Resultsmentioning
confidence: 99%
“…Inoculation of the forage by lactic acid bacteria improves both the fermentation process and aerobic stability (Muck et al, 2018). The selection of highly competitive strains (Carvalho et al, 2020) can improve the production of lactic acid as well as that of other organic acids able to inhibit the proliferation of undesirable fungi (Guimarães et al, 2018). Driehuis et al (1999) observed that strains of Lentilactobacillus buchneri ( Lactobacillus buchneri (Zheng et al, 2020)) were able to degrade lactic acid into acetic acid and 1,2‐propanediol (Oude Elferink et al, 2001), which could then be metabolized into propionic acid (Krooneman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, obligately heterofermentative LAB are mainly used to improve aerobic stability due to the production of acetic acid and propionic acid, which has an antifungal effect [1]. The phylogenetic relationships among the validated species in the current study, the main LABs [26] that have been evaluated as silage inoculants, and the LABs in CSI are shown in Fig. 3.…”
Section: Discussionmentioning
confidence: 91%